Counterweight Reinforcement versus Slope Geometry Redesign for the Block 16 Sidewall at PT XYZ - Bambang Heriyadi; Rinaldo Maretto Patar Simangunsong; Yozsi Mingsi Aneperta; Heri Prabowo; Fariz Aditya (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2026)
Landslides occurred on the Block 16 sidewall at PT XYZ, where the upper benches comprise low-stability fill and the lower benches comprise bedded rock. This study characterized the rock mass, assessed discontinuity-controlled failure potential, calibrated the failed-slope condition by back analysis, and compared counterweight reinforcement with slope-geometry redesign. Scanline mapping, Rock Mass Rating (RMR), stereographic kinematic analysis, Slope Mass Rating (SMR), and Bishop-simplified limit-equilibrium simulations in Slide 6.0 were applied. The lower rock benches had an average RMR of 69.5 and an SMR of 68.6. Oblique-toppling criteria were satisfied by 7.62% of the analyzed discontinuities. The initial model yielded an SF of 1.239, while back analysis reproduced the failure condition at SF = 0.995. Counterweighting increased SF to 1.324 using 42.6 m³/m of fill; geometry redesign produced SF = 1.352 with 264.98 m³/m of excavation. Both alternatives met the SF > 1.3 criterion, but counterweighting required substantially less material handling.